Pragmatic integration of user-centered design and implementation science: A new methodological approach for clinical decision support implementation in EHRs - Maw, Anna; Hoppe, Jason; Wagner, Nicole; Mitchell, James; Bean, Meagan; Trinkley, Katy E. (Applied Clinical Informatics)
Background Clinical decision support (CDS) tools are critical for improving care delivery and guideline adherence but are associated with clinician burnout when inadequately designed and implemented. User Centered Design (UCD) and Implementation Science (IS) methods are evidence-based approaches to optimizing CDS tools, but are infrequently used in part due to limited guidance on how to apply them within the resource-constraints of health systems. Objective This paper focuses on pragmatic application of an integrated UCD-IS approach, demonstrating how it can be adapted to meet operational constraints through two real world case studies. Methods We applied an integrated UCD-IS approach guided by the Practical Robust Implementation and Sustainability Model (PRISM) to two CDS projects within a large regional health system: (1) adapting a CDS for improving prescribing of goal-directed medical therapy in patients with heart failure during virtual visits, and (2) expanding a naloxone co-prescribing CDS across outpatient settings. Each project followed iterative phases—partner engagement, design, prototyping, deployment, and evaluation tailored to time and resource constraints of the health system. Methods used included interviews, focus groups, surveys, and usability testing. Results Multilevel partner engagement surfaced critical insights that informed design adaptations. The heart failure CDS was adapted using minimal changes while the naloxone CDS underwent more extensive design iterations. Both projects balanced rigor and pragmatism, enabling timely implementation and rigorous design evaluation while supporting feasibility and sustainability. Iterative evaluations of both CDS are ongoing and structured to inform real-time refinements that support patient, clinician, and system level outcomes. Conclusions This work provides practical guidance on applying an integrated UCD-IS approach to CDS design and evaluation in time and resource-constrained health system environments. By flexibly applying this integrated approach, health systems can better address multilevel partner needs, ensure contextual relevance, and support sustained adoption.